A linguagem dos quadrinhos como instrumento de mediação didática para os estudos da relação cidade e campo no ensino de geografia - Silva, Ykaro Feliphe Sousa (2024)
This study is based on the concern about the need to promote the formation of concepts in the teaching-learning process of Geography, from a critical perspective, with a view to meaningful learning. In this sense, different languages have been appropriated by primary school teachers as pedagogical and didactic aids for the intended formation to take place. Among these is the language of comics, a textual genre that arouses interest and curiosity and often deals with political, social and environmental issues, making it a tool with great potential for critical reflection. This language can be represented by comics, cartoons, graphic novels, manga and caricatures, which, when used appropriately as a tool in the didactic mediation process of the geography teacher, can contribute to the development of students' critical thinking, the formation of geographical thinking, enabling the development of students as critical and autonomous citizens, capable of reading, thinking and situating themselves in the world, understanding and analyzing their daily lives and exercising citizenship. In view of the above, this research was guided by the objective of understanding the potential of comic language as a didactic mediation tool for the formation of concepts about the relationship between city and countryside and its contributions to the formation of geographical thinking. To achieve this, we used a qualitative methodology, document analysis of the geography textbooks used from 6th to 9th grade in the city of Minaçu-GO, where the researcher works as a teacher of this curricular component, and the curriculum document for Goiás (2018), participant research, elaboration and analysis of the application of a didactic course on the relationship between city and countryside in a municipal public school in the city of Minaçu/GO. The results showed that although comics are considered an alternative language in the curriculum, they do not have a significant presence in geography textbooks, including in the content of the relationship between the city and the countryside. Based on the literature review, the language of comics can be considered as a potential tool for didactic mediation, as long as the teacher is fully prepared and has mastered the content and language used. Through the application of the didactic pathway with students in the 7th year of primary school, there was evidence of the formation of concepts of the relationship between the city and the countryside after this process.